In vitro propagation of Paphiopedilum orchids. (3rd May 2016) - Zeng, Songjun; Huang, Weichang; Wu, Kunlin; Zhang, Jianxia; Teixeira da Silva, Jaime A.; Duan, Jun
Abstract: Paphiopedilum is one of the most popular and rare orchid genera. Members of the genus are sold and exhibited as pot plants and cut flowers. Wild populations of Paphiopedilum are under the threat of extinction due to over-collection and loss of suitable habitats. A reduction in their commercial value through large-scale propagation in vitro is an option to reduce pressure from illegal collection, to attempt to meet commercial needs and to re-establish threatened species back into the wild. Although they are commercially propagated via asymbiotic seed germination, Paphiopedilum are considered to be difficult to propagate in vitro, especially by plant regeneration from tissue culture. This review aims to cover the most important aspects and to provide an up-to-date research progress on in vitro propagation of Paphiopedilum and to emphasize the importance of further improving tissue culture protocols for ex vitro -derived explants.